Peran perpustakaan sekolah dalam meningkatkan minat literasi siswa di SD Muhammadiyah Plus Kota Salatiga - Silfana Wiwit Soliha (Librarium: Library and Information Science Journal, 2026)
The school library serves as a pivotal educational pillar, offering dynamic learning spaces and comprehensive resources to foster students' literacy. This study investigates the role of the library at SD Muhammadiyah Plus Kota Salatiga in enhancing students’ literacy interest through innovative programs like "Daun Taro." Using qualitative methods, including interviews and direct observations, this research analyzes the library's services, their effectiveness, and their alignment with students' needs. Results indicate that strategic programs such as mobile book carts, digital services, and literacy competitions significantly increase students' reading enthusiasm. Collaborative efforts with teachers and parents further strengthen the school’s literacy culture. These findings highlight the library's transformative role in not only promoting reading habits but also nurturing critical and creative thinking skills. The study concludes by recommending continued innovations and collaborations to sustain and expand the library's impact.